Identification of amino acid residues of nerve growth factor important for neurite outgrowth in human dorsal root ganglion neurons. (1st August 2019) - Dahlström, Märta; Nordvall, Gunnar; Sundström, Erik; Åkesson, Elisabet; Tegerstedt, Gunilla; Eriksdotter, Maria; Forsell, Pontus
Abstract: Nerve growth factor (NGF) is an essential neurotrophic factor for the development and maintenance of the central and the peripheral nervous system. NGF deficiency in the basal forebrain precedes degeneration of basal forebrain cholinergic neurons in Alzheimer's disease, contributing to memory decline. NGF mediates neurotrophic support via its high‐affinity receptor, the tropomyosin‐related kinase A (TrkA) receptor, and mediates mitogenic and differentiation signals via the extracellular signal‐regulated protein kinases 1 and 2 (ERK1/2). However, the molecular mechanisms underlying the different NGF/TrkA/ERK signalling pathways are far from clear. In this study, we have investigated the role of human NGF and three NGF mutants, R100E, W99A and K95A/Q96A, their ability to activate TrkA or ERK1/2, and their ability to induce proliferation or differentiation in human foetal dorsal root ganglion (DRG) neurons or in PC12 cells. We show that the R100E mutant was significantly more potent than NGF itself to induce proliferation and differentiation, and significantly more potent in activation of ERK1/2 in DRG neurons. The W99A and K95A/Q96A mutants, on the other hand, were less effective than the wild‐type protein. An unexpected finding was the high efficacy of the K95A/Q96A mutant to activate TrkA and to induce differentiation of DRG neurons at elevated concentrations. These data demonstrate an NGF mutant with improved neurotrophic properties in primary human neuronal cells. The R100E mutant represents an interesting candidate for further drug development in Alzheimer's disease and other neurodegenerative disorders. Abstract : The nerve growth factor (NGF) mutant R100E is more potent to induce proliferation, differentiation (anti‐β‐tubulin green staining) and phosphorylation of ERK1/2 (red staining) than wild‐type NGF in human foetal dorsal root ganglion (DRG) neurons after a 4‐day treatment. The NGF double mutant K95A/Q96A is more efficient to induce neuronal differentiation than wild‐type NGF in DRG neurons at high concentrations (>3 μg/ml). We show enhanced functional response in human nerve cells with NGF mutants.